Pengaruh Motivasi, Kreativitas dan Inovasi terhadap Minat Berwirausaha Siswa (Studi pada SMK Negeri 1 Bandar Dua Kabupaten Pidie Jaya) - Erdalina, Eva; Azhari, Azhari; Musrizal, Musrizal (Aceh Cooperative Care, 2023)
This research was conducted on students of SMK Negeri 1 Bandar Dua, Pidie Jaya Regency, Aceh Province by studying students' interest in entrepreneurship. In this research, we want to know the influence of student motivation, creativity and innovation factors. Of the 221 students, 100 students were taken as samples spread across each grade level. The data collection technique uses a questionnaire, with a type of verification research based on causality analysis between variables so that the analysis technique uses a path analysis model. The research results showed that: (1) there was a positive and significant influence of motivational factors on interest in entrepreneurship of 47.744%. (2) there is a positive and significant influence of the creativity aspect on interest in entrepreneurship of 19.656%. 3) the level of student innovation influences interest in entrepreneurship with a contribution of 7.910%. And (4) together students' motivation, creativity and innovation make a high contribution to interest in entrepreneurship, namely 75.1%.